Serum leptin and triglyceride levels in patients on treatment with atypical antipsychotics - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B (Physicians Postgraduate Press, 2003)
Background: Weight gain is a common adverse effect associated with the use of most antipsychotic drugs. Leptin has been reported to be associated with antipsychotic-induced weight gain. Previous studies have demonstrated a relationship between the atypical antipsychotics clozapine and olanzapine and serum leptin levels. We planned to comparatively investigate the effects of the atypical antipsychotics quetiapine, olanzapine, risperidone, and clozapine on leptin and triglyceride levels and weight gain. Method: The study population comprised 56 patients with DSM-IV schizophrenia, who were divided into 4 treatment groups: quetiapine (N = 14), olanzapine (N = 14), risperidone (N = 14), or clozapine (N = 14) monotherapy, and a control group of 11 patients receiving no psychopharmacologic treatment. The patients were evaluated at baseline and at the sixth week according to the Positive and Negative Syndrome Scale (PANSS). body mass index (BMI), weight, and fasting serum leptin and triglyceride levels. Data were gathered in 2001 and 2002. Results: Olanzapine and clozapine caused a marked increase in weight and serum triglyceride and leptin levels, though increases in these variables were modest in the patients receiving quetiapine and minimal in those receiving risperidone. There were positive correlations between serum leptin levels and BMI and triglyceride levels. Clinical efficacy, as indicated by decrease in total PANSS scores, was associated with leptin levels in all atypical antipsychotic groups. Conclusion: Our results suggest that leptin may be associated with olanzapine- and clozapine-induced weight gain and that quetiapine appears to have modest influence and risperidone appears to have minimal influence on leptin and triglyceride levels and weight gain compared with olanzapine and clozapine.
Keywords: Body-Weight Gain; Plasma-Levels; Serotonin; Mechanisms; Cytokine; Insulin; Obesity; Cholesterol; Endocrine; Clozapine